Profits of deceit: Performing populism in polarised times. (December 2020) - Murdock, Graham
The article is an invited contribution to the special issue to mark the anniversary of the publication of Jim McGuigan's 'Cultural Populism'. Drawing on work on authoritarian populism produced by the scholars grouped around the Frankfurt Institute of Research during their war-time exile in the Unites States, this article explores the right-wing populist platforms developed by Donald Trump during and after his presidential campaign and by the two Leave campaigns in the British referendum on European Union membership. It argues that understanding their popular appeal requires us to pay particular attention to the performative styles employed and the ways they mobilise motifs from popular media and direct forms of communicative address to connect with lived experiences, articulate anxieties and present policies that benefit the already privileged as true expressions of the popular interest.